Physical activity promotion interventions in chronic airways disease: a systematic review and meta-analysis. (25th January 2023) - Reilly, Caroline; Sails, Joe; Stavropoulos-Kalinoglou, Antonios; Birch, Rebecca J.; McKenna, Jim; Clifton, Ian J.; Peckham, Daniel; Birch, Karen M.; Price, Oliver J.
Physical inactivity is common in people with chronic airways disease (pwCAD) and associated with worse clinical outcomes and impaired quality of life. We conducted a systematic review and meta-analysis to characterise and evaluate the effectiveness of interventions promoting step-based physical activity (PA) in pwCAD. We searched for studies that included a form of PA promotion and step-count outcome measure. A random-effects model was used to determine the overall effect size using post-intervention values. 38 studies (n=32 COPD; n=5 asthma; n=1 bronchiectasis; study population: n=3777) were included. Overall, implementing a form of PA promotion resulted in a significant increase in step-count: median (IQR) 705 (183–1210) when compared with usual standard care: −64 (−597–229), standardised mean difference (SMD) 0.24 (95% CI: 0.12–0.36), p<0.01. To explore the impact of specific interventions, studies were stratified into subgroups: PA promotion+wearable activity monitor-based interventions (n=17) (SMD 0.37, p<0.01); PA promotion+step-count as an outcome measure (n=9) (SMD 0.18, p=0.09); technology-based interventions (n=12) (SMD 0.16, p=0.01). Interventions promoting PA, particularly those that incorporate wearable activity monitors, result in a significant and clinically meaningful improvement in daily step-count in pwCAD. Utilising wearable activity monitors in conjunction with established behaviour change techniques leads to the greatest improvement in step-based physical activity in people with chronic airways disease. https://bit.ly/3Ujs8y7